Finalursachen in der frühen Neuzeit : eine Untersuchung der Transformation teleologischer Erklärungen - Schmid, Stephan (Quellen und Studien zur Philosophie ;, 2011)
By reconstructing the teleological conceptions of Thomas Aquinas, Suarez, Descartes, Spinoza, and Leibniz, the author argues against the common view that mechanical philosophers in the Early Modern period rejected natural teleology because of its association with an Aristotelian picture of the world. First, many thinkers in the Early Modern period did not reject teleological explanations for natural phenomena. Second, many scholastic thinkers already believed that pure natural teleology was problematic because they held that authentic teleological explanations are only possible when goals can.